The Dow is Killing Me: Risky Health Behaviors and the Stock Market. (7th May 2014) - Cotti, Chad; Dunn, Richard A.; Tefft, Nathan
Abstract We investigate how risky health behaviors and self‐reported health vary with the Dow Jones Industrial Average (DJIA) and during stock market crashes. Because stock market indices are leading indicators of economic performance, this research contributes to our understanding of the macroeconomic determinants of health. Existing studies typically rely on the unemployment rate to proxy for economic performance, but this measure captures only one of many channels through which the economic environment may influence individual health decisions. We find that large, negative monthly DJIA returns, decreases in the level of the DJIA, and stock market crashes are widely associated with worsening self‐reported mental health and more cigarette smoking, binge drinking, and fatal car accidents involving alcohol. These results are consistent with predictions from rational addiction models and have implications for research on the association between consumption and stock prices. Copyright © 2014 John Wiley & Sons, Ltd.